2013
DOI: 10.1159/000354375
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Rowland Universal Dementia Assessment Scale for Multicultural Screening in Danish Memory Clinics

Abstract: Background/Aims: The Rowland Universal Dementia Assessment Scale (RUDAS) is a brief cognitive screening test that was developed to detect dementia in multicultural populations. The RUDAS has not previously been validated in multicultural populations outside of Australia. The aim of this study was to evaluate the diagnostic accuracy of the RUDAS in a multicultural sample of patients referred to Danish memory clinics. Methods: Data were collected from 137 consecutive patients (34 with an immigrant background) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 43 publications
4
47
1
Order By: Relevance
“…Finally, the RUDAS has previously been evaluated in clinical settings - either specialist memory clinics or general aged care referrals. For those studies using a similar methodology to the current study (i.e., considering a diagnosis of dementia compared to no dementia, not excluding CIND or MCI), sensitivity ranged from 64 to 89% and specificity from 77 to 98% [7,14,15,19]. Our results for the RUDAS in a nonclinical community setting are within these ranges at 71.4% sensitivity and 90.3% specificity.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Finally, the RUDAS has previously been evaluated in clinical settings - either specialist memory clinics or general aged care referrals. For those studies using a similar methodology to the current study (i.e., considering a diagnosis of dementia compared to no dementia, not excluding CIND or MCI), sensitivity ranged from 64 to 89% and specificity from 77 to 98% [7,14,15,19]. Our results for the RUDAS in a nonclinical community setting are within these ranges at 71.4% sensitivity and 90.3% specificity.…”
Section: Discussionsupporting
confidence: 63%
“…The RUDAS [7] is a cognitive screening tool that was specifically designed to minimize the impact of cultural differences on test performance. It has been validated in culturally diverse groups, both in Australia [14,15,16], where it was initially developed, and internationally [17,18,19]. RUDAS performance is not associated with cultural or language background in multicultural settings [14,15,19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study (n = 137) looked specifically at the immigrancy status of participants 26 and showed that test performance on the RUDAS was not significantly affected (p = 0.08), whereas it was on the MMSE (p = 0.02).…”
Section: Immigrant Statusmentioning
confidence: 99%